USP15 stabilizes TGF-β receptor I and promotes oncogenesis through the activation of TGF-β signaling in glioblastoma - Eichhorn, Pieter J A; Rodón, Laura; Gonzàlez-Juncà, Alba; Dirac, Annette; Gili, Magüi; Martínez-Sáez, Elena; Aura, Claudia; Barba, Ignasi; Peg, Vicente; Prat, Aleix; Cuartas, Isabel; Jimenez, Jose; et al. (Nature medicine, 2012)
TGF-β signaling is commonly aberrantly activated in gliomas and other tumors and can exert a pro-oncogenic function. The authors identify a new mechanism for upregulation of TGF-β signaling in cancer. The deubiquitinase USP15 is shown to be able to bind the TGF-β receptor complex, counteract its degradation and potentiate its stimulation of downstream mediators. USP15 is amplified in human glioblastoma and could represent a therapeutic target, as its downregulation impairs the growth of glioblastoma cells in vivo . In advanced cancer, including glioblastoma, the transforming growth factor β (TGF-β) pathway acts as an oncogenic factor and is considered to be a therapeutic target. Using a functional RNAi screen, we identified the deubiquitinating enzyme ubiquitin-specific peptidase 15 (USP15) as a key component of the TGF-β signaling pathway. USP15 binds to the SMAD7–SMAD specific E3 ubiquitin protein ligase 2 (SMURF2) complex and deubiquitinates and stabilizes type I TGF-β receptor (TβR-I), leading to an enhanced TGF-β signal. High expression of USP15 correlates with high TGF-β activity, and the USP15 gene is found amplified in glioblastoma, breast and ovarian cancer. USP15 amplification confers poor prognosis in individuals with glioblastoma. Downregulation or inhibition of USP15 in a patient-derived orthotopic mouse model of glioblastoma decreases TGF-β activity. Moreover, depletion of USP15 decreases the oncogenic capacity of patient-derived glioma-initiating cells due to the repression of TGF-β signaling. Our results show that USP15 regulates the TGF-β pathway and is a key factor in glioblastoma pathogenesis.